2019
DOI: 10.3390/ijms20194967
|View full text |Cite
|
Sign up to set email alerts
|

Dec1 Deficiency Suppresses Cardiac Perivascular Fibrosis Induced by Transverse Aortic Constriction

Abstract: Cardiac fibrosis is a major cause of cardiac dysfunction in hypertrophic hearts. Differentiated embryonic chondrocyte gene 1 (Dec1), a basic helix–loop–helix transcription factor, has circadian expression in the heart; however, its role in cardiac diseases remains unknown. Therefore, using Dec1 knock-out (Dec1KO) and wild-type (WT) mice, we evaluated cardiac function and morphology at one and four weeks after transverse aortic constriction (TAC) or sham surgery. We found that Dec1KO mice retained cardiac funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Although Dec1 is well known as an oncogene in tumors ( Nakamura et al, 2008 ; Feige et al, 2011 ; Sato et al, 2016 ; Jia et al, 2018 ), the present study also adds to a growing body of molecular evidence linking Dec1 to hypoxia-associated diseases ( Nishiyama et al, 2012 ; Wu et al, 2017 ; Huang et al, 2018 ; Nakashima et al, 2018 ; Le et al, 2019 ). For example, Hue et al previously reported that Dec1 expression was significantly upregulated in human cardiac hypertrophy and myocardial infarction, while Dec1 deficiency suppressed cardiac perivascular fibrosis and attenuated expressions of p21, TGF-β1, pSmad3, and TNF-α in transverse aortic constriction treated mouse models ( Le et al, 2019 ). Although the potential mechanism remained to be specified, this study provided key findings regarding Dec1 in transverse aortic constriction induced by hypoxia, inflammation, and fibrosis in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Although Dec1 is well known as an oncogene in tumors ( Nakamura et al, 2008 ; Feige et al, 2011 ; Sato et al, 2016 ; Jia et al, 2018 ), the present study also adds to a growing body of molecular evidence linking Dec1 to hypoxia-associated diseases ( Nishiyama et al, 2012 ; Wu et al, 2017 ; Huang et al, 2018 ; Nakashima et al, 2018 ; Le et al, 2019 ). For example, Hue et al previously reported that Dec1 expression was significantly upregulated in human cardiac hypertrophy and myocardial infarction, while Dec1 deficiency suppressed cardiac perivascular fibrosis and attenuated expressions of p21, TGF-β1, pSmad3, and TNF-α in transverse aortic constriction treated mouse models ( Le et al, 2019 ). Although the potential mechanism remained to be specified, this study provided key findings regarding Dec1 in transverse aortic constriction induced by hypoxia, inflammation, and fibrosis in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 80%
“…Differentiated embryo-chondrocyte expressed gene 1 is dysregulated by hypoxia-driven responses and plays important roles in cell death and survival ( Park and Park, 2012 ; Sato et al, 2016 ; Jia et al, 2018 ; Nakashima et al, 2018 ; Le et al, 2019 ). Therefore, the hnPAECs were treated with hypoxia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation has been known to precede cardiac fibrosis in TAC mice 36 ; therefore, we investigated the accumulation of T cells and macrophages in the heart after TAC. In the immunohistochemical analysis of CD3 and CD68 in heart sections, the infiltration of T cells and macrophages occurred in TAC mice, and they were both observed in the cardiac tissues after TAC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Human differentiated embryonic chondrocyte expressed gene 1 (DEC1), also known as BHLHE40/Stra13/Sharp2, belongs to a structurally distinct class of basic helix- loop-helix (bHLH) proteins ( Sato et al, 2016 ). It has been considered as a signaling mediator of diverse physiological processes including circadian rhythmicity, immunity, proliferation, apoptosis, senescence, tumorigenesis, and fibrosis ( Honma et al, 2002 ; Qian et al, 2008 ; Gallo et al, 2018 ; Jia et al, 2018 ; Jarjour et al, 2019 ; Le et al, 2019 ; Li et al, 2019 ). A previous study has reported that Dec1 deficiency suppressed cardiac perivascular fibrosis in hypertrophic hearts induced by transverse aortic constriction (TAC), resulting in preserved cardiac function ( Le et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%